Design and Implementation of a DC–DC resonant LLC converter for electric vehicle fast chargers - Rocha, João (2025)
This article presents the design and implementation of a DC–DC power converter for application in electric vehicle (EV) fast-charging systems. The prototype is of the resonant LLC type and consists of a high-power transformer operating at high frequency, which is an essential feature for the adequate behavior of the EV fast-charging system as a whole. As demonstrated throughout the article, by using this converter topology as well as its specific operating modes, such as for achieving zero-voltage switching (ZVS) and zero-current switching (ZCS), it is possible to enhance efficiency by reducing conduction and switching losses as well as to increase power density. The details of the high-power high-frequency transformer (HFT), considering different designs, are presented and discussed. With the implemented laboratorial prototype fully developed with silicon carbide (SiC) power semiconductor devices, it was possible to demonstrate and validate the main features of the resonant LLC converter, including high efficiency, under distinct conditions of operation.